What should be the economic priorities in post-war Ukraine? - Christopher A. Hartwell; Dmytro Boyarchuk (EconPol Forum, 2023)
Ukraine must first win the war. But if it can successfully expel Russia from all of its territories, it needs to accelerate its post-Maidan, pre-war tempo of reforms. Ukraine must build what it has long been lacking: the rule of law. In order to do this, it must build the rule of law from scratch, reforming its judiciary, unabashedly protecting property rights, and continuing its highly successful decentralization reforms. During the transition from war economy to market economy, simplification of nearly every facet of interaction with the government should be undertaken - and kept in place. This will encourage not just hanging on to foreign charity, but also encourage investments needed for growth. These steps will help Ukraine move towards Europe and continue its march towards Euro-integration even if (and especially if) accession to the European Union is a longerterm goal. Ukraine's survival after the war is dependent on making policy reversals incredibly difficult to implement. This requires substantial political will
Keywords: 330